Emotional Elements in Cukup Derita Itu by Siti Rosmizah Semail - Idrus, Azean Idruwani; Abdull Asik, Asma Nur Husna (Malay Literature, 2023)
In a production of a literary work, an author normally uses emotional elements as the main medium to convey messages, ideas and worldviews about his or her writing. Emotions that exist in human beings are elements of their natural instincts that are gifted by Allah SWT. These emotional elements function and act in the reader’s mind when he or she is reading a literary work. Following that, this study focuses on the emotional elements found in the characters in the novel Cukup Derita Itu by Siti Rosmizah Semail by applying the sense-phenomenology theory by Sohaimi Abdul Aziz (1998) to support the criticism and analysis of the text in a structured manner. The method used in this study is qualitative in the form of text-centred descriptive analysis. The results of the analysis found that there are three emotional elements that are highlighted in Cukup Derita Itu, namely the emotions of grief, lust and hatred that affect the characters. These emotions appear because of the events experienced by the characters. The implications of this study summarize that the emotions of grief, lust and uncontrollable hatred can change a person’s behaviour. The study also shows that emotions are complex because a person’s external characteristics do not necessarily reflect the emotions he or she is experiencing. Full text :  PDF